2022
DOI: 10.1371/journal.pone.0263462
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic and evolutionary analyses of detoxification gene families in Aphidinae species

Abstract: Detoxification enzymes play significant roles in the interactions between insects and host plants, wherein detoxification-related genes make great contributions. As herbivorous pests, aphids reproduce rapidly due to parthenogenesis. They are good biological materials for studying the mechanisms that allow insect adaptation to host plants. Insect detoxification gene families are associated with insect adaptation to host plants. The Aphidinae is the largest subfamily in the Aphididae with at least 2483 species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
1
13
1
Order By: Relevance
“…The fewer detoxification-related genes may be due to the unobvious duplication events of detoxification-related genes. Genes with conserved roles usually have relatively stable copies, while those with diversified functions have higher rates of gain-and-loss with random changing degrees [ 56 ]. The numbers of ABCs of S. chinensis was 55, that was more than other aphids and showed significant genetic expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fewer detoxification-related genes may be due to the unobvious duplication events of detoxification-related genes. Genes with conserved roles usually have relatively stable copies, while those with diversified functions have higher rates of gain-and-loss with random changing degrees [ 56 ]. The numbers of ABCs of S. chinensis was 55, that was more than other aphids and showed significant genetic expansion.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that gene duplications were critical for the evolution of new genes and novel functions and were major forces driving gene family expansion [ 60 ]. For example, CYP genes, often clustering in genomes, were considered as a result of gene duplication events [ 56 ]. We calculated the Ka and Ks values to estimate the evolutionary trend and revealed a functional selection pressure between duplicated gene pairs.…”
Section: Discussionmentioning
confidence: 99%
“…After gene annotation, phylogenetic analyses are performed to analyze the diversification pattern using nucleotide or amino acid sequence alignments. The resulting phylogenetic trees will reveal genes that are conserved and those that have duplicated in a lineage-specific manner, which might be linked to the emergence of an evolutionarily novel function in PSM detoxification and sequestration (e.g., Ahn et al, 2019;Yang et al, 2021;Lin et al, 2022). Gene family evolution can also be analyzed using CAFE (Computational Analysis of gene Family Evolution), a statistical method that estimates gene gains and losses across a species phylogeny based on birth and death models (Bie et al, 2006;Han et al, 2013).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…After gene annotation, phylogenetic analyses are performed to analyze the diversification pattern using nucleotide or amino acid sequence alignments. The resulting phylogenetic trees will reveal genes that are conserved and those that have duplicated in a lineage-specific manner, which might be linked to the emergence of an evolutionarily novel function in PSM detoxification and sequestration (e.g., Ahn et al, 2019;Yang et al, 2021;Lin et al, 2022). Gene family evolution can also be analyzed using CAFÉ (Computational Analysis of gene Family Evolution), a statistical method that estimates gene gains and losses across a species phylogeny based on birth and death models (Bie et al, 2006;Han et al, 2013).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%